Training load and submaximal heart rate testing throughout a competitive period in a top-level male football team - Rago, V.; Krustrup, P.; Martin-Acero, R.; Rebelo, A.; Mohr, M. (Journal of Sports Sciences, 2020)
The aim of this study was to investigate training load and cardiorespiratory fitness in a top-level Spanish (LaLiga) football team (n = 17). The submaximal Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1SUB) was performed in four moments of the competitive period from early February (E1) to early May (E4). Training load was quantified using a 10-Hz global positioning system and heart rate (HR) recording (n = 837 individual training sessions), while match load was quantified using semi-automated cameras (n = 216 individual match observations). Cardiorespiratory fitness moderately improved as the season progressed (P < 0.05; effect sizes = 0.8 to 1.2). Cumulative total distance covered during training between E1 and E4 was negatively correlated with percentage of changes in mean HR during the last 30 s of Yo-Yo IR1SUB (P = 0.049; r = -0.47 [-0.71; -0.14]; moderate). HR during the last 30 s of Yo-Yo IR1SUB was negatively correlated to total distance covered during the match (P = 0.024; r = -0.56 [-0.80; -0.17]; moderate). Yo-Yo IRSUB can be used to monitor seasonal changes in cardiorespiratory fitness without the need to have players work until exhaustion. Cardiorespiratory fitness given by mean HR during the last 30 s of the test seems meaningful in relation to match performance.